Influence of chemical machining on axial fatigue behaviour of electron beam melted Ti6Al4V parts. (January 2023) - Manco, Emanuele; Scherillo, Fabio; Guerrera, Chiara; Bruno, Matteo; El Hassanin, Andrea; Franchitti, Stefania; Borrelli, Rosario; Esposito, Luca
Graphical abstract: Abstract: Additive manufacturing of titanium parts is a technology widely adopted and investigated because of the great demand of advanced components from aerospace, biomedical and automotive industry. Among the technologies available for additive manufacturing, Electron Beam Melting can produce high density components in short time, however surface quality is poor and incompatible with industrial requirements. For this reason, surface finishing is generally required. In this work, a chemical surface treatment by means of chemical machining has been investigated on specimens built according to axial fatigue standard geometry, and their fatigue behaviour has been correlated with surface quality.